Electromagnetic shielding composite paper and preparation method thereof
By combining basalt fibers with aramid nanofibers and carbon nanotubes, and vacuum-assisted filtration and hot pressing treatment, high-performance electromagnetic shielding composite paper is prepared, which solves the problems of high production costs and weak interface combinations in the prior art, and achieves long-term stable electromagnetic shielding performance and structural integrity in extreme environments.
Patent Information
- Application Number
- CN202310726231.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-06-19
AI Technical Summary
The existing electromagnetic shielded paper-based materials have high production costs, and basalt fibers have problems such as weak interface bonding and easy agglomeration when making paper.
By dispersing basalt fibers in the aramid nanofiber dispersion liquid, mixing them with the carbon nanotube dispersion liquid, and following vacuum-assisted filtration and hot pressing treatment, electromagnetic shielding composite paper with excellent electromagnetic shielding performance and mechanical properties was prepared.
It realizes long-term stable electromagnetic shielding performance and structural integrity in extreme environments, reduces production costs, overcomes the problems of uneven dispersion and easy agglomeration of basalt fibers and carbon nanotubes, and improves the mechanical properties and electromagnetic shielding performance of the material.
Smart Images

Figure CN116752380B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the intersecting field of electromagnetic shielding materials and papermaking technology, and in particular to an electromagnetic shielding composite paper and a preparation method thereof. Background Art
[0002] With the popularization of electronic devices and the rapid development of 5G communication systems, electromagnetic waves play an increasingly important role in modern society. However, they also bring some negative effects. Electromagnetic interference (EMI) not only poses potential hazards to human health, but also causes mutual interference problems between electronic devices. In addition, the accumulated heat and thermal failures of wearable electronic devices during long-term operation pose a fire risk. Rubber and plastics, such as styrene-butadiene rubber (SBR), polypropylene (PP) and polystyrene (PS), have traditionally been used as substrates for making flexible electromagnetic shielding materials. However, their poor thermal stability and non-biodegradability limit their application. Therefore, in order to effectively protect against electromagnetic wave pollution, it is necessary to use electromagnetic shielding technology to develop green, high-performance, extreme environment-resistant, and lightweight electromagnetic shielding materials to protect against electromagnetic wave pollution.
[0003] Traditional electromagnetic shielding materials, such as metal materials, have shortcomings such as easy corrosion, high density and high price, which limit their application in some occasions. In recent years, the research on electromagnetic shielding composite paper has become a hot topic and has been widely used in anti-static packaging materials, electromagnetic shielding materials, new energy and electrochemical materials. In the application of electromagnetic shielding materials, the lightweight, high-performance and multi-purpose application of electromagnetic shielding materials has become an important development trend. Paper-based materials have a unique three-dimensional network structure, adjustable composition, structure and thickness, and can also be recycled. As an effective and practical material for EMI shielding applications, it has attracted great attention, especially in portable devices, flexible protective materials, aircraft and aerospace fields. It has broad application prospects. Paper-based materials are usually made of plant fibers, synthetic fibers or mineral materials as the main raw materials, with advantages such as light weight, low density and easy processing. However, plant fibers have poor temperature resistance and can only be used in occasions with low temperature requirements. The paper-based materials prepared with high-performance organic fiber-aramid fiber are relatively expensive and have poor electromagnetic shielding performance. As a relatively inexpensive, high-performance, green and environmentally friendly fiber, basalt fiber has excellent temperature resistance and dielectric properties, and is expected to improve the overall temperature resistance of the material and product differentiation.
[0004] Basalt fiber (BF) is an emerging high-performance inorganic fiber with the characteristics of environmental protection and pollution-free. It is known as the "green industrial material of the 21st century". The fiber has high modulus, high strength, electrical insulation performance, excellent chemical stability, good heat resistance (-265℃~800℃), low thermal conductivity, and low moisture absorption rate. It has broad application prospects in fireproofing and heat insulation, high-temperature filtration, filtration environmental protection, construction materials, electronic technology, electrical insulation and other fields. At present, basalt fiber is mainly used in the fields of wastewater treatment, sound absorption and wear-resistant materials, and has received continuous attention. But so far, there are very few reports on its application in electromagnetic shielding materials under extreme environments. However, the surface of basalt fiber is smooth and has poor hydrophilicity, which easily causes polarization of water molecules, making the fiber surface negatively charged, and then leads to static electricity between fibers, mutual entanglement, easy agglomeration and difficult dispersion, resulting in weak interfacial bonding of basalt fiber in paper production. The difficulties and challenges faced in interfacial bonding limit its application in the papermaking industry. Summary of the invention
[0005] The present invention provides an electromagnetic shielding composite paper which can exhibit long-term stable electromagnetic shielding performance and structural integrity under extreme environments, and has high strength, high toughness and high shielding effectiveness, and a preparation method thereof, so as to solve the problems of high production cost of existing electromagnetic shielding paper-based materials and weak interface bonding and easy agglomeration of basalt fibers during papermaking.
[0006] To achieve the above object, the present invention provides a method for preparing an electromagnetic shielding composite paper, comprising:
[0007] a) dispersing basalt fibers in aramid nanofiber dispersion to form a mixed dispersion;
[0008] b) dispersing the carbon nanotubes in an organic solvent to form a carbon nanotube dispersion;
[0009] c) mixing the mixed dispersion and the carbon nanotube dispersion, washing, and desolventizing;
[0010] d) dispersing the filter cake obtained by desolventizing in deionized water, vacuum filtering, and drying to obtain base paper;
[0011] e) subjecting the base paper to heat pressing treatment to obtain electromagnetic shielding composite paper.
[0012] Aramid fibers are deprotonated using dimethyl sulfoxide to prepare aramid nanofibers, and then basalt fibers are mixed with aramid nanofibers to obtain a mixed dispersion, and then the mixed dispersion is mixed with a carbon nanotube dispersion, and electromagnetic shielding composite paper is obtained by vacuum-assisted filtration and hot pressing. The above preparation method solves the problem that traditional paper-based materials are not resistant to high temperature and acid-base corrosion, reduces the production cost of aramid paper, and overcomes the problems of uneven dispersion and easy agglomeration of carbon nanotubes and basalt fibers. The prepared electromagnetic shielding composite paper is a flexible material with the characteristics of easy processing, wide shielding frequency band, and good shielding performance. It has high strength, high toughness, and high shielding effectiveness, and can show long-term stable electromagnetic shielding performance and structural integrity in extreme environments. It can be used as a material to prevent electromagnetic wave pollution and shows excellent electromagnetic shielding performance and mechanical properties.
[0013] As a further improvement, the mass ratio of basalt fiber to aramid nanofiber is 1:(1-4); the content of carbon nanotubes in the electromagnetic shielding composite paper is 10-80% (such as 10%, 37%, 50%, 55.5%, 63%, 80% or any value therebetween).
[0014] In a further improvement, the preparation of the mixed dispersion in step a) comprises the following steps:
[0015] a1) mixing aramid fibers, potassium hydroxide, dimethyl sulfoxide and deionized water to crack the aramid fibers and form an aramid nanofiber dispersion;
[0016] a2) dispersing the basalt fibers in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion.
[0017] Basalt fiber has the characteristics of high modulus, high strength, excellent chemical stability, good heat resistance, etc. However, the surface of basalt fiber is smooth and chemically inert, and it is difficult to form surface bonding with other materials. Aramid nanofibers are used as the reinforcing phase, and a large number of active groups on the surface of aramid nanofibers are utilized to make the basalt fibers evenly dispersed and physically interwoven with aramid nanofibers, which effectively solves the problem of basalt fibers being easy to agglomerate and difficult to disperse. It can significantly improve the interface bonding problem of basalt fibers in paper-based materials, and is beneficial to enhancing the mechanical properties of electromagnetic shielding composite paper.
[0018] As a further improvement, in step a1), the ratio of aramid fiber, potassium hydroxide, dimethyl sulfoxide and deionized water is (0.5-4) g: (1-3) g: (400-800) mL: (10-50) mL.
[0019] Further improvement, in step a1), the mixing and stirring conditions are: room temperature, magnetic stirring rate of 1000-2000r / min, and time of 3-5h; in step a2), the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min.
[0020] As a further improvement, the preparation of the carbon nanotube dispersion in step b) includes the following steps: adding carbon nanotubes into an organic solvent, adding a dispersant thereto, dispersing the carbon nanotubes by ultrasonic treatment, and forming a carbon nanotube dispersion with a carbon nanotube concentration of 0.13 to 1 g / L.
[0021] Carbon nanotubes are highly valued for their excellent electrical conductivity, thermal conductivity, mechanical strength, low density and large surface area. When added to composite materials, they can make the materials show good electromagnetic shielding performance. However, carbon nanotubes are easy to aggregate and difficult to disperse due to their unique chemical structure and surface inertness. Dispersants can improve the dispersion of carbon nanotubes. Carbon nanotubes are compounded with basalt fibers and aramid nanofibers to make the electromagnetic shielding composite paper have excellent electromagnetic shielding performance and mechanical properties, and are easy to carry.
[0022] Further improvement, in step b), the organic solvent is ethanol or dimethyl sulfoxide; the dispersant is at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, and the added amount of the dispersant is 5-20% of the mass of the carbon nanotubes; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min.
[0023] Furthermore, the organic solvent is preferably dimethyl sulfoxide; the dispersant is preferably polyvinyl pyrrolidone. The use of organic solvents and dispersants to disperse carbon nanotubes can fully disperse the carbon nanotubes, increase their dispersion in the dispersion, and enable the carbon nanotube powder in the filter cake formed in the subsequent steps to be fully dispersed and decomposed without aggregation and entanglement.
[0024] As a further improvement, the specific operation of step c) is as follows: the mixed dispersion and the carbon nanotube dispersion are mixed under mechanical stirring conditions, and then the obtained mixed solution is added dropwise into deionized water under magnetic stirring conditions, and then rinsed with water and ethanol alternately for 5 to 10 times. After the rinsing is completed, the solvent is removed by vacuum filtration to obtain a filter cake for standby use.
[0025] After the mixed liquid is rinsed alternately for multiple times, the solvent is removed by vacuum filtration, which allows the carbon nanotubes, basalt fibers and aramid nanofibers to be repeatedly and alternately infiltrated, filled and combined with water and ethanol, so that the aramid nanofibers and carbon nanotubes can be more fully and evenly interspersed in the pores of the basalt fiber skeleton, thereby avoiding the degradation of the mechanical properties of the composite material and improving the structural stability of the electromagnetic shielding composite paper. At the same time, the improvement of internal dispersion uniformity also improves the electromagnetic shielding performance and electromagnetic shielding stability of the electromagnetic shielding composite paper.
[0026] As a further improvement, in step c), the mechanical stirring speed is 1000-8000 r / min for 5-30 min; the magnetic stirring speed is 500-2000 r / min; and the dropwise addition speed of the mixed solution is 10-20 mL / min.
[0027] As a further improvement, in step d), the dispersion concentration of the filter cake is 0.05-0.5 g / L, the drying temperature is 80-120° C., and the time is 8-20 min. Preferably, in step d), the filter cake is dispersed by mechanical stirring, the rotation speed of the mechanical stirring is 1000-8000 r / min, and the stirring time is 5-30 min.
[0028] As a further improvement, in step e), the hot pressing treatment conditions are: pressure of 5-20 MPa, temperature of 30-120°C, and time of 5-60 min. After hot pressing, the carbon nanotubes and aramid nanofibers build a stable 3D interconnected conductive network on the basalt fiber skeleton, improving the interface properties and mechanical properties of the aramid paper-based material, and obtaining an electromagnetic shielding composite paper with high performance electromagnetic shielding.
[0029] On the other hand, the present invention also provides an electromagnetic shielding composite paper, which is prepared by the aforementioned method for preparing the electromagnetic shielding composite paper; the thickness of the electromagnetic shielding composite paper is 0.02 to 0.2 mm (such as 0.02 mm, 0.05 mm, 0.1 mm, 0.13 mm, 0.2 mm or any thickness therebetween); the electromagnetic shielding composite paper has a total electromagnetic shielding effectiveness of 10 to 60 dB for a frequency of 8.2 to 12.4 GHz.
[0030] The electromagnetic shielding composite paper of the present invention is a flexible material with a dense surface and strong interface adhesion between the components, and can maintain excellent electromagnetic shielding performance and structural integrity in extreme environments (including fire, high / low temperature and acid-base corrosion).
[0031] Furthermore, the present invention also provides the application of the electromagnetic shielding composite paper in the field of smart film, personal thermal management or wearable electromagnetic protection. The electromagnetic shielding composite paper can also be applied to many fields such as 5G telecommunication substrate, electromagnetic shielding material, protective material, interior material and electronic product substrate.
[0032] The electromagnetic shielding composite paper and the preparation method thereof provided by the present invention achieve the following beneficial effects:
[0033] 1) This preparation method uses basalt fiber as the skeleton of electromagnetic shielding composite paper, interspersed between the films formed by aramid nanofibers and carbon nanotubes, forming an interlaced "reinforced concrete" structure, which can significantly improve the bonding strength of each component and also improve the environmental stability and structural stability of electromagnetic shielding composite paper under extreme conditions. Through vacuum-assisted filtration and hot pressing treatment, the electromagnetic shielding composite paper has a layered structure, which prolongs the propagation path of electromagnetic waves and is conducive to the absorption and dissipation of electromagnetic waves.
[0034] 2) This preparation method overcomes the problems of uneven dispersion and easy agglomeration of basalt fibers and carbon nanotubes, and solves the problems of traditional paper-based electromagnetic shielding materials being not resistant to high temperatures and acid-base corrosion, and having poor flexibility, effectively improving the electromagnetic shielding performance and mechanical properties of paper-based materials, and expanding the application range of electromagnetic shielding composite paper. Moreover, this method has abundant raw material sources, simple and fast operation, easier and more flexible process, low cost, high yield, and is easy for large-scale production.
[0035] 3) The electromagnetic shielding composite paper cleverly integrates the excellent conductivity, mechanical properties, shielding properties of carbon nanotubes and the excellent chemical stability and weather resistance of basalt fibers, so that an entangled network is formed between the basalt fibers and the carbon nanotubes, which fully exerts the electromagnetic shielding effect of the carbon nanotubes and basalt fibers. Electromagnetic waves are continuously reflected and transmitted in the electromagnetic shielding composite paper, and are continuously attenuated to produce multiple reflection and transmission losses, thereby achieving the purpose of resisting electromagnetic wave interference. The electromagnetic shielding composite paper exhibits long-term stable electromagnetic shielding performance and structural integrity in various extreme environments (including fire, high / low temperature and acid-base corrosion), and also exhibits excellent Joule heating performance, rapid electrothermal response and good temperature controllability.
[0036] 4) The electromagnetic shielding composite paper has the characteristics of light weight, strong weather resistance, wide shielding frequency band and good shielding performance. It not only has 10~40S·cm -1 It has high conductivity and high electromagnetic interference shielding effectiveness (EMI SE) of 10-60dB, and exhibits 5000-20000dB·cm at a thickness of 0.02-0.2μm. 2 ·g -1 It has high specific shielding effectiveness (SSE / t) and can be further processed into flexible electromagnetic shielding products in different forms. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 Surface and cross-sectional SEM images of the electromagnetic shielding composite paper with 30% carbon nanotube content prepared in Example 5, a1-surface, a2-cross-sectional;
[0039] Figure 2 The average electromagnetic shielding effectiveness diagram of electromagnetic shielding composite papers with different carbon nanotube contents prepared in Examples 4 to 8;
[0040] Figure 3 The graphs are the relationship between the specific shielding effectiveness and the frequency of the electromagnetic shielding composite papers with different carbon nanotube contents prepared in Examples 4 to 8;
[0041] Figure 4 The relationship between the total shielding effectiveness and the frequency of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4, Example 9 and Example 10 at different thicknesses;
[0042] Figure 5 The photographs of the electromagnetic shielding composite paper prepared in Example 4 and Comparative Example 1 before and after being ignited on an alcohol lamp for 120 seconds, (a) - Example 4, (b) - Comparative Example 1;
[0043] Figure 6 This is a graph showing the change in total shielding effectiveness of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after being ignited by an alcohol lamp;
[0044] Figure 7 This is a diagram showing the shielding effectiveness change of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after treatment under extreme high / low temperature conditions;
[0045] Figure 8 This is a diagram showing the shielding effectiveness change of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after treatment under extreme acid and alkali conditions;
[0046] Fig. 9 This is a temperature-time relationship diagram of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 when a gradient voltage is applied;
[0047] Fig.10 This is the tensile stress-strain diagram of the electromagnetic shielding composite paper with a carbon nanotube content of 30% prepared in Example 5. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present invention.
[0049] The following examples use conventional instruments and equipment in the art. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources, and their specifications are conventional specifications in the art. If no specific techniques or conditions are specified in the following examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0050] It should be noted that, in the present invention and the following embodiments, concentrations, ratios, etc. not otherwise specified are all weight concentrations, weight ratios, etc., "%" means weight percentage, and "parts" means parts by weight, which are common writing habits used by those skilled in the art and are therefore not described in detail in the present invention.
[0051] In a specific embodiment, the method for preparing the electromagnetic shielding composite paper of the present invention comprises the following steps:
[0052] 1) Aramid fiber, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed and stirred at room temperature and a stirring rate of 1000-2000 r / min for 3-5 hours to crack the aramid fiber and form an aramid nanofiber dispersion; the ratio of the aramid fiber, potassium hydroxide, dimethyl sulfoxide and deionized water is (0.5-4) g: (1-3) g: (400-800) mL: (10-50) mL.
[0053] Preferably, the ratio of aramid fiber, potassium hydroxide, dimethyl sulfoxide and deionized water is 1 g:1.5 g:500 mL:20 mL.
[0054] 2) Dispersing the basalt fiber in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion. The mass ratio of the basalt fiber to the aramid nanofiber is 1:(1-4); the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min. The mass ratio of the basalt fiber to the aramid nanofiber can be 1:1, 1:1.3, 1:1.5, 1:2, 1:2.6, 1:3.3, 1:4 or any value therebetween.
[0055] 3) Adding carbon nanotubes into an organic solvent, and then adding a dispersant of 5-20% of the mass of carbon nanotubes thereto, dispersing the carbon nanotubes by ultrasonic treatment to form a carbon nanotube dispersion liquid with a carbon nanotube concentration of 0.13-1 g / L. The organic solvent is ethanol or dimethyl sulfoxide; the dispersant is at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min.
[0056] 4) The mixed dispersion and the carbon nanotube dispersion are mechanically stirred and mixed at a rotation speed of 1000 to 8000 r / min for 5 to 30 minutes, and then the obtained mixed solution is added dropwise to deionized water at a speed of 10 to 20 mL / min under magnetic stirring at a speed of 500 to 2000 r / min, and then rinsed with water and ethanol alternately for 5 to 10 times. After the rinsing is completed, the solvent is removed by vacuum filtration to obtain a filter cake for standby use.
[0057] 5) dispersing the filter cake obtained by desolventization in deionized water with a mechanical stirring speed of 1000-8000 r / min for 5-30 min, vacuum filtering, and drying at a temperature of 80-120° C. for 8-20 min to obtain base paper; the dispersion concentration of the filter cake is 0.05-0.5 g / L (such as 0.1 g / L, 0.15 g / L, 0.25 g / L, 0.3 g / L, 0.36 g / L, 0.4 g / L, 0.43 g / L or any value therebetween).
[0058] 6) The base paper is hot-pressed for 5 to 60 minutes at a pressure of 5 to 20 MPa and a temperature of 30 to 120° C. to obtain an electromagnetic shielding composite paper with a thickness of 0.02 to 0.2 mm (such as 0.02 mm, 0.05 mm, 0.1 mm, 0.13 mm, 0.2 mm or any thickness therebetween) and a carbon nanotube content of 10 to 80% (such as 10%, 37%, 50%, 55.5%, 63%, 80% or any value therebetween).
[0059] It should be noted that, in the present invention, the sources of basalt fiber, aramid fiber and carbon nanotube are not particularly limited, and their specifications are not particularly limited. Preferably, the diameter of the carbon nanotube is 10-50nm and the length is 15-40μm; the carbon nanotube is a multi-walled carbon nanotube or a single-walled carbon nanotube. Preferably, the diameter of the basalt fiber is 10-20μm and the length is 5-35mm. Preferably, the diameter of the aramid fiber is 10-25μm and the length is 3-15mm.
[0060] It should be noted that there is no time sequence limitation for step a) and step b) of the present invention; step a) and step b) may also be performed simultaneously.
[0061] The present invention is further described in detail below in conjunction with the examples. However, it should be understood that the examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0062] Embodiment 1:
[0063] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0064] 1) 0.5 g aramid fiber, 1 g potassium hydroxide, 400 mL dimethyl sulfoxide, and 10 mL deionized water were mixed and stirred at room temperature and a stirring rate of 1000 r / min for 5 h to pyrolyze the aramid fiber and form an aramid nanofiber dispersion.
[0065] 2) Dispersing the basalt fibers in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion. The mass ratio of the basalt fibers to the aramid nanofibers is 1:1; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300 W, and time of 15 min.
[0066] 3) Add the carbon nanotubes into an organic solvent, add a dispersant of 5% by mass of the carbon nanotubes, and disperse the carbon nanotubes by ultrasonic treatment to form a carbon nanotube dispersion with a carbon nanotube concentration of 0.13 g / L. The organic solvent is ethanol; the dispersant is sodium dodecyl sulfate; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300 w, and time of 15 min.
[0067] 4) The mixed dispersion and the carbon nanotube dispersion were mechanically stirred for 30 min at a rotation speed of 1000 r / min, and then the obtained mixed solution was added dropwise into deionized water at a speed of 10 mL / min under a magnetic stirring condition of a speed of 500 r / min, and then rinsed with water and ethanol alternately for 5 times. After the rinsing was completed, the solvent was removed by vacuum filtration to obtain a filter cake for standby use.
[0068] 5) The filter cake obtained by desolventization was dispersed in deionized water by mechanical stirring at a speed of 1000 r / min for 30 min, and after vacuum filtration, it was dried at a temperature of 80° C. for 20 min to obtain base paper; the dispersion concentration of the filter cake was 0.05 g / L.
[0069] 6) The base paper was subjected to hot pressing treatment at a pressure of 5 MPa and a temperature of 30° C. for 60 min to obtain an electromagnetic shielding composite paper with a thickness of 0.02 mm and a carbon nanotube content of 10%.
[0070] Embodiment 2:
[0071] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0072] 1) 4 g of aramid fiber, 3 g of potassium hydroxide, 800 mL of dimethyl sulfoxide, and 50 mL of deionized water were mixed and stirred at room temperature and a stirring rate of 2000 r / min for 3 h to pyrolyze the aramid fiber and form an aramid nanofiber dispersion.
[0073] 2) Dispersing the basalt fibers in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion. The mass ratio of the basalt fibers to the aramid nanofibers is 1:4; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 600 W, and time of 5 min.
[0074] 3) Add the carbon nanotubes into an organic solvent, add a dispersant of 20% of the mass of the carbon nanotubes, and disperse the carbon nanotubes by ultrasonic treatment to form a carbon nanotube dispersion with a carbon nanotube concentration of 1 g / L. The organic solvent is dimethyl sulfoxide; the dispersant is sodium dodecylbenzene sulfonate; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 600w, and time of 5 minutes.
[0075] 4) The mixed dispersion and the carbon nanotube dispersion were mechanically stirred at a rotation speed of 8000 r / min for 5 min, and then the obtained mixed solution was added dropwise to deionized water at a speed of 20 mL / min under magnetic stirring at a speed of 2000 r / min, and then rinsed with water and ethanol alternately for 10 times. After the rinsing was completed, the solvent was removed by vacuum filtration to obtain a filter cake for standby use.
[0076] 5) The filter cake obtained by desolventization was dispersed in deionized water by mechanical stirring at a speed of 8000 r / min for 5 minutes, and after vacuum filtration, it was dried at a temperature of 120° C. for 8 minutes to obtain base paper; the dispersion concentration of the filter cake was 0.5 g / L.
[0077] 6) The base paper was subjected to hot pressing treatment at a pressure of 20 MPa and a temperature of 120° C. for 5 minutes to obtain an electromagnetic shielding composite paper with a thickness of 0.2 mm and a carbon nanotube content of 80%.
[0078] Embodiment 3:
[0079] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0080] 1) 2.5 g of aramid fiber, 2 g of potassium hydroxide, 600 mL of dimethyl sulfoxide, and 30 mL of deionized water were mixed and stirred at room temperature and a stirring rate of 1500 r / min for 4.5 h to pyrolyze the aramid fiber and form an aramid nanofiber dispersion.
[0081] 2) Dispersing the basalt fibers in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion. The mass ratio of the basalt fibers to the aramid nanofibers is 1:2.5; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 400 W, and time of 10 min.
[0082] 3) Add the carbon nanotubes into an organic solvent, add a dispersant of 15% of the mass of the carbon nanotubes, and disperse the carbon nanotubes by ultrasonic treatment to form a carbon nanotube dispersion with a carbon nanotube concentration of 0.5 g / L. The organic solvent is ethanol; the dispersant is polyvinyl pyrrolidone; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 500 W, and time of 10 min.
[0083] 4) The mixed dispersion and the carbon nanotube dispersion were mechanically stirred for 15 min at a rotation speed of 6000 r / min, and then the obtained mixed solution was added dropwise into deionized water at a speed of 15 mL / min under magnetic stirring at a speed of 1500 r / min, and then rinsed with water and ethanol alternately for 8 times. After the rinsing was completed, the solvent was removed by vacuum filtration to obtain a filter cake for standby use.
[0084] 5) The filter cake obtained by desolventization was dispersed in deionized water by mechanical stirring at a speed of 3000 r / min for 15 min, and after vacuum filtration, it was dried at a temperature of 100° C. for 10 min to obtain base paper; the dispersion concentration of the filter cake was 0.35 g / L.
[0085] 6) The base paper was hot-pressed at a pressure of 15 MPa and a temperature of 100° C. for 45 min to obtain an electromagnetic shielding composite paper with a thickness of 0.08 mm and a carbon nanotube content of 55%.
[0086] Embodiment 4:
[0087] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0088] 1) 1 g of aramid fiber, 1.5 g of potassium hydroxide, 500 mL of dimethyl sulfoxide, and 20 mL of deionized water were mixed and stirred at room temperature and a stirring rate of 1000 r / min for 4 h to pyrolyze the aramid fiber and form a dark red aramid nanofiber dispersion with an aramid fiber concentration of 0.2%.
[0089] 2) 20 mL of the aramid nanofiber dispersion prepared in step 1) was measured, and 0.013 g of basalt fiber (the mass ratio of basalt fiber to aramid nanofiber was 1:3) was weighed, and the basalt fiber was dispersed in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion. The ultrasonic treatment conditions were: room temperature, ultrasonic power of 400 W, and time of 10 min.
[0090] 3) 0.07 g of multi-walled carbon nanotubes were added to dimethyl sulfoxide, and then 0.007 g of polyvinyl pyrrolidone (i.e., 10% by mass of carbon nanotubes) was added thereto, and the carbon nanotubes were dispersed by ultrasonic treatment to form a carbon nanotube dispersion with a carbon nanotube concentration of 0.4 g / L. The ultrasonic treatment conditions were: room temperature, ultrasonic power of 400 W, and time of 10 min.
[0091] 4) The mixed dispersion and the carbon nanotube dispersion were mechanically stirred and mixed at a rotation speed of 3000 r / min for 20 min, and then the obtained mixed solution was dropwise added into deionized water at a speed of 20 mL / min under a magnetic stirring condition at a speed of 1000 r / min, and then rinsed with water and ethanol alternately for 6 times. After the rinsing was completed, the solvent was removed by vacuum filtration to obtain a filter cake for standby use.
[0092] 5) The filter cake obtained by desolventization was dispersed in deionized water by mechanical stirring at a speed of 4000 r / min for 20 min, and after vacuum filtration, it was dried at a temperature of 105° C. for 10 min to obtain base paper; the dispersion concentration of the filter cake was 0.2 g / L.
[0093] 6) The base paper was subjected to hot pressing treatment at a pressure of 10 MPa and a temperature of 60° C. for 30 minutes to obtain an electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 60%.
[0094] Embodiment 5:
[0095] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0096] 1) is the same as step 1) of Example 4;
[0097] 2) The only difference from step 2) of Example 4 is that: 34 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.022 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0098] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.04 g of multi-walled carbon nanotubes and 0.004 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0099] 4) is the same as step 4) of Example 4;
[0100] 5) is the same as step 5) of Example 4;
[0101] 6) is different from step 6) of embodiment 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 30% is obtained by hot pressing.
[0102] Embodiment 6:
[0103] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0104] 1) is the same as step 1) of Example 4;
[0105] 2) The only difference from step 2) of Example 4 is that: 29 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.019 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0106] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.05 g of multi-walled carbon nanotubes and 0.005 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0107] 4) is the same as step 4) of Example 4;
[0108] 5) is the same as step 5) of Example 4;
[0109] 6) is different from step 6) of embodiment 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 40% is obtained by hot pressing.
[0110] Embodiment 7:
[0111] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0112] 1) is the same as step 1) of Example 4;
[0113] 2) The only difference from step 2) of Example 4 is that: 24 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.016 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0114] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.06 g of multi-walled carbon nanotubes and 0.006 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0115] 4) is the same as step 4) of Example 4;
[0116] 5) is the same as step 5) of Example 4;
[0117] 6) is different from step 6) of embodiment 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 50% is obtained by hot pressing.
[0118] Embodiment 8:
[0119] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0120] 1) is the same as step 1) of Example 4;
[0121] 2) The only difference from step 2) of Example 4 is that: 15 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.01 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0122] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.09 g of multi-walled carbon nanotubes and 0.009 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0123] 4) is the same as step 4) of Example 4;
[0124] 5) is the same as step 5) of Example 4;
[0125] 6) is different from step 6) of embodiment 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 70% is obtained by hot pressing.
[0126] Embodiment 9:
[0127] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0128] 1) is the same as step 1) of Example 4;
[0129] 2) The only difference from step 2) of Example 4 is that: 59 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.039 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0130] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.234 g of multi-walled carbon nanotubes and 0.0234 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0131] 4) is the same as step 4) of Example 4;
[0132] 5) is the same as step 5) of Example 4;
[0133] 6) is different from step 6) of embodiment 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.123 mm and a carbon nanotube content of 60% is obtained by hot pressing.
[0134] Embodiment 10:
[0135] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0136] 1) is the same as step 1) of Example 4;
[0137] 2) The only difference from step 2) of Example 4 is that: 98 mL of the aramid nanofiber dispersion prepared in step 1) is measured, 0.065 g of basalt fiber is weighed (the mass ratio of basalt fiber to aramid nanofiber is 1:3), and the basalt fiber is dispersed in the prepared aramid nano dispersion by ultrasonic treatment;
[0138] 3) The only difference from step 3) of Example 4 is that the carbon nanotube dispersion contains 0.39 g of multi-walled carbon nanotubes and 0.039 g of polyvinyl pyrrolidone (i.e., 10% by weight of carbon nanotubes);
[0139] 4) is the same as step 4) of Example 4;
[0140] 5) is the same as step 5) of Example 4;
[0141] 6) is different from step 6) of Example 4 only in that: the electromagnetic shielding composite paper with a thickness of 0.157 mm and a carbon nanotube content of 60% is obtained by hot pressing.
[0142] Comparative Example 1:
[0143] A method for preparing aramid nanofiber / carbon nanotube electromagnetic shielding composite paper comprises the following steps:
[0144] 1) is the same as step 1) of Example 4;
[0145] 2) is the same as step 3) of Example 4;
[0146] 3) The only difference from step 4) of Example 4 is that: 98 mL of the aramid nanofiber dispersion prepared in step 1) is measured and the aramid nanofiber dispersion and the carbon nanotube dispersion are mixed;
[0147] 4) is the same as step 5) of Example 4;
[0148] 5) The only difference from step 6) of Example 4 is that the aramid nanofiber / carbon nanotube electromagnetic shielding composite paper with a thickness of 0.04 mm and a carbon nanotube content of 60% is obtained by hot pressing.
[0149] Comparative Example 2:
[0150] A method for preparing electromagnetic shielding composite paper comprises the following steps:
[0151] 1) is the same as step 1) of Example 4;
[0152] 2) is the same as step 2) of Example 4;
[0153] 3) is the same as step 3) of Example 4;
[0154] 4) is different from step 4) of Example 4 only in that: the mixed dispersion and the carbon nanotube dispersion are mechanically stirred and mixed at a rotation speed of 3000 r / min for 20 min, and then the resulting mixed solution is added dropwise to deionized water at a rate of 20 mL / min under magnetic stirring at a speed of 1000 r / min, and then the solvent is removed by vacuum filtration to obtain a filter cake for standby use.
[0155] 5) is the same as step 5) of Example 4;
[0156] 6) is the same as step 6) of Example 4.
[0157] Test Example 1:
[0158] Microstructure of electromagnetic shielding composite paper
[0159] Characterization method: Use field emission scanning electron microscope (SEM, TESCAN, 5kV) to scan and take the scanning electron microscope image of electromagnetic shielding composite paper. The sample is sprayed with gold for 45s and the acceleration voltage is 5kV. The electromagnetic shielding composite paper prepared in Example 5 is used as the sample. The results are shown in Figure 1 shown.
[0160] Figure 1 The surface and cross-sectional SEM images of the electromagnetic shielding composite paper with 30% carbon nanotube content prepared in Example 5, a1-surface, a2-cross-sectional. Figure 1It can be seen that the basalt fibers overlap each other to form the skeleton of the electromagnetic shielding composite paper; aramid nanofibers and carbon nanotubes are filled in these skeletons to form a "reinforced concrete" structure, thereby significantly improving the stability of the electromagnetic shielding composite paper in extreme environments. From the cross-sectional SEM image of a2, it can be seen that the electromagnetic shielding composite paper forms a multi-layer structure under vacuum filtration and hot pressing treatment. The layered structure extends the propagation path of electromagnetic waves, which is conducive to the absorption and consumption of electromagnetic waves, and is more conducive to the formation of multiple reflections of electromagnetic waves inside the material, and attenuation, so that the electromagnetic shielding composite paper obtains better electromagnetic shielding performance.
[0161] Test Example 2:
[0162] Electromagnetic shielding performance test
[0163] Test method: Rohde & Schwarz ZNB20 vector network analyzer was used to obtain scattering parameters (S11 and S21) in the frequency range of 8.2 to 12.4 GHz (X band) by waveguide method to evaluate the electromagnetic shielding performance of electromagnetic shielding composite paper. The samples were electromagnetic shielding composite papers prepared in Examples 4 to 10 and Comparative Example 2. The samples were cut into 23 mm × 10 mm rectangular specimens for testing. Three parallels were set for each test example, and the average value was taken. The results are shown in Figure 1. Figure 2 , Figure 3 , Figure 4 , as shown in Table 1.
[0164] The thickness of electromagnetic shielding composite paper is measured in accordance with the provisions of (GB / T451.2-1989). Use a thickness tester to measure the sample, read the reading and make a record, read 5 data for each sample, take the average value, the unit is mm.
[0165] The power coefficients of reflection (R), transmission (T), and absorption (A), as well as the total EMI SE (SET), reflection SE (SER), and absorption SE (SEA) are calculated as follows:
[0166] R=|S 11 | 2 (1);
[0167] T=|S 21 | 2 (2);
[0168] 1 = A + R + T (3);
[0169] SE T =SE A +SE R +SE M (4);
[0170] SER = -10log|1-R| (5);
[0171] SE A = -10log|T / (1-R)| (6);
[0172] Among them, SE M represents the multiple reflection SE between the two surfaces of the paper. If SE T ≥15dB, SE can be ignored M In addition, the specific shielding effectiveness (SSE / t) was calculated using the following equation:
[0173] SSE / t=SE T / (ρt) (7);
[0174] Where ρ and t represent the density of the sample (g·cm -3 ) and thickness (cm).
[0175] Figure 2 The average electromagnetic shielding effectiveness diagram of electromagnetic shielding composite papers with different carbon nanotube contents prepared in Examples 4 to 8. Figure 2 It can be seen that with the increase of carbon nanotube content, the conductive network formed inside the electromagnetic shielding composite paper is more perfect, SE T , SE A , SE R Are gradually increasing.
[0176] Figure 3 The graphs are the relationship between the specific shielding effectiveness and the frequency of the electromagnetic shielding composite papers with different carbon nanotube contents prepared in Examples 4 to 8. Figure 3 It can be seen that with the increase of carbon nanotube content, the specific shielding effectiveness of the electromagnetic shielding composite paper is gradually increasing.
[0177] Figure 4 The relationship between the total shielding effectiveness and frequency of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Examples 4, 9 and 10 at different thicknesses is shown. Figure 4 It can be seen that with the increase of the thickness of the electromagnetic shielding composite paper, the overall shielding effectiveness increases significantly.
[0178] Table 1 Test results of electromagnetic shielding performance of different electromagnetic shielding composite papers
[0179] <![CDATA[SE T (dB)]]> <![CDATA[SE A (dB)]]> <![CDATA[SE R (dB)]]> <![CDATA[SSE / t(dB·cm 2 ·g -1 )]]> Example 4 22.25 9.12 13.13 12.67k Comparative Example 2 18.56 6.38 12.18 7.38k
[0180] It can be seen from Table 1 that the electromagnetic shielding performance of the electromagnetic shielding composite paper prepared in Comparative Example 2 without alternate washing with water and ethanol is significantly lower than that of Example 4. It can be seen that the use of multiple alternate washings with water and ethanol in the present invention is beneficial to the full and uniform interpenetration of the three components in the electromagnetic shielding composite paper, which is beneficial to improving the dispersion uniformity inside the electromagnetic shielding composite paper, and is also beneficial to improving its electromagnetic shielding performance and electromagnetic shielding stability.
[0181] Test Example 3:
[0182] Electromagnetic shielding performance and structural integrity testing in extreme environments
[0183] (1) Fire environment
[0184] Test method: The samples are the electromagnetic shielding composite papers prepared in Example 4 and Comparative Example 1. The samples are cut into semicircular samples with a diameter of 20 mm. The samples are placed on the flame of a lit alcohol lamp for 120 seconds, and their appearance changes are observed. The total shielding effectiveness of the samples of Example 4 before and after being placed on the flame is tested using the method of Test Example 2. The results are shown in Figure 2. Figure 5 , Figure 6 shown.
[0185] Figure 5 The following are photos of the electromagnetic shielding composite paper prepared in Example 4 and Comparative Example 1 before and after being ignited on an alcohol lamp for 120 seconds, (a) - Example 4, (b) - Comparative Example 1. Figure 5 It can be seen that after the electromagnetic shielding composite paper of Example 4 was ignited on the alcohol lamp for 120 seconds, it still maintained its intact shape without any cracking, while the electromagnetic shielding composite paper of Comparative Example 1 was severely cracked. It can be seen that after the basalt fiber was introduced into the electromagnetic shielding composite paper, the high temperature resistance of the electromagnetic shielding composite paper was significantly improved, and the high temperature environment stability of the electromagnetic shielding composite paper was greatly enhanced.
[0186] Figure 6 This is a graph showing the change in total shielding effectiveness of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after being ignited by an alcohol lamp. Figure 6 It can be seen that after being ignited on the alcohol lamp for 120 seconds, the electromagnetic shielding composite paper still maintains its intact shape without any cracking. By measuring the electromagnetic shielding effectiveness of the electromagnetic shielding composite paper before and after ignition, it is found that the overall shielding effectiveness decreases slightly, but the difference with the shielding effectiveness before ignition is not significant, and the electromagnetic shielding effectiveness of the samples before and after ignition above 11.5 GHz is basically the same, indicating that the electromagnetic shielding composite paper of Example 4 prepared by the method of the present invention has extremely strong environmental stability.
[0187] (2) Extreme high / low temperature environment
[0188] Test method: The sample is the electromagnetic shielding composite paper prepared in Example 4, and the sample is cut into a rectangular sample of 35mm×15mm. Before the test, the shielding effectiveness of the sample is tested using the method of Test Example 2, and then the samples are randomly divided into two groups. One group of samples is thermally annealed at 300℃ for 6 hours, and the other group of samples is immersed in liquid nitrogen for 1 hour. After the treatment, the samples are taken out and the shielding effectiveness of the treated samples is tested. The results are as follows: Figure 7 shown.
[0189] Figure 7 This is a diagram showing the shielding effectiveness change of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after treatment under extreme high / low temperature conditions. Figure 7 It can be seen that after being treated under extreme high / low temperature conditions, the shielding effectiveness of the electromagnetic shielding composite paper decreases slightly, but the difference in shielding effectiveness compared with before treatment under extreme high / low temperature conditions is not significant, indicating that the electromagnetic shielding composite paper has extremely strong resistance to high / low temperature.
[0190] (3) Extreme acid and alkali corrosion environment
[0191] Test method: The sample is the electromagnetic shielding composite paper prepared in Example 4, and the sample is cut into a 35mm×15mm sample. Before the test, the shielding effectiveness of the sample is tested using the method of Test Example 2, and then the samples are randomly divided into two groups. One group of samples is immersed in an acidic solution (sulfuric acid solution) with a pH of 1 for 20 hours, and the other group of samples is immersed in an alkaline solution (sodium hydroxide solution) with a pH of 14 for 20 hours. After the treatment, the samples are taken out and the shielding effectiveness of the treated samples is tested. The results are as follows: Figure 8 shown.
[0192] Figure 8 This is a diagram showing the shielding effectiveness change of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 before and after treatment under extreme acid and alkali conditions. Figure 8 It can be seen that after being treated under strong acid and alkaline conditions, the shielding effectiveness of the electromagnetic shielding composite paper decreases slightly, but the difference in shielding effectiveness before treatment under extreme acid and alkaline conditions is not significant, indicating that the electromagnetic shielding composite paper has extremely strong resistance to acid and alkali corrosion.
[0193] Test example 4:
[0194] Temperature responsiveness test
[0195] Test method: The sample is the electromagnetic shielding composite paper prepared in Example 4. The electrothermal conversion performance of the electromagnetic shielding composite paper is studied at a certain voltage using a DC power supply (MS-6050, MAISHANG), and the temperature of the electromagnetic shielding composite paper is measured using an infrared thermal imager (FLIRi7). Gradient voltages of 6V, 8V, 10V, 12V, and 14V are applied to the sample, each voltage lasts for 30s, and the temperature change of the sample under each voltage is tested. The results are shown in Figure 2. Fig. 9 shown.
[0196] Fig. 9 This is a temperature-time relationship diagram of the electromagnetic shielding composite paper with a carbon nanotube content of 60% prepared in Example 4 when a gradient voltage is applied. Fig. 9 It can be seen that the electromagnetic shielding composite paper has a fast temperature response under different voltages, indicating that the electromagnetic shielding composite paper has good temperature controllability.
[0197] Test Example 5:
[0198] Mechanical properties test
[0199] Test method: The samples are the electromagnetic shielding composite papers prepared in Example 4, Example 5 and Comparative Example 2. The samples are cut into rectangular specimens of 15 mm × 30 mm. The tensile strength is evaluated using a tensile tester (AI-7000-NGD, Goodtechwell) at a speed of 5 mm / min. The results are shown in Fig.10 , as shown in Table 2.
[0200] Fig.10 This is the tensile stress-strain diagram of the electromagnetic shielding composite paper with a carbon nanotube content of 30% prepared in Example 5. Fig.10 It can be seen that the electromagnetic shielding composite paper prepared by the present invention has good mechanical strength.
[0201] Table 2 Tensile properties test results of different electromagnetic shielding composite papers
[0202] Example 4 Example 5 Comparative Example 2 Tensile stress MPa 53.71 54.62 43.57 Elongation at break % 3.21 3.14 2.61
[0203] It can be seen from Table 2 that the tensile properties of the electromagnetic shielding composite paper prepared in Comparative Example 2 without alternate washing with water and ethanol are significantly lower than those of Examples 4 and 5 of the present invention. It can be seen that the use of multiple alternate washings with water and ethanol in the present invention is beneficial to the full and uniform interpenetration of the three components in the electromagnetic shielding composite paper, which is beneficial to improving the dispersion uniformity inside the electromagnetic shielding composite paper, avoiding the degradation of the mechanical properties of the composite material, and improving the structural stability of the electromagnetic shielding composite paper.
[0204] It should be noted that in the present invention, the detailed steps of some operations are not described in detail, but belong to the prior art known to those skilled in the art, so they will not be repeated here. In addition, in the present invention, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values (including integers and fractions) within the range.
[0205] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. In the present invention, not all possible combinations of the various technical features in the various embodiments or embodiments are described. As long as there is no contradiction in the combination of these technical features, the various technical features in the various embodiments or embodiments can be arbitrarily combined, and all possible combinations should be considered to be within the scope of this specification. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing electromagnetic shielding composite paper, characterized in that: The steps include: a) dispersing basalt fibers in aramid nanofiber dispersion to form a mixed dispersion; b) dispersing the carbon nanotubes in an organic solvent to form a carbon nanotube dispersion; c) mixing the mixed dispersion and the carbon nanotube dispersion, washing, and desolventizing; d) dispersing the filter cake obtained by desolventizing in deionized water, vacuum filtering, and drying to obtain base paper; e) subjecting the base paper to a heat-pressing treatment to obtain the electromagnetic shielding composite paper; The mass ratio of the basalt fiber to the aramid nanofiber is 1:(1-4); The content of carbon nanotubes in the electromagnetic shielding composite paper is 10-80%; The specific operation of step c) is: mixing the mixed dispersion and the carbon nanotube dispersion under mechanical stirring conditions, then dropping the obtained mixed solution into deionized water under magnetic stirring conditions, and then washing with water and ethanol alternately for 5 to 10 times. After the washing is completed, vacuum filtration is performed to remove the solvent to obtain a filter cake for standby use.
2. The method for preparing the electromagnetic shielding composite paper according to claim 1, characterized in that: The preparation of the mixed dispersion in step a) comprises the following steps: a1) mixing aramid fibers, potassium hydroxide, dimethyl sulfoxide and deionized water to crack the aramid fibers and form an aramid nanofiber dispersion; a2) dispersing the basalt fibers in the aramid nanofiber dispersion by ultrasonic treatment to form a mixed dispersion.
3. The method for preparing the electromagnetic shielding composite paper according to claim 2, characterized in that: In the step a1), the ratio of aramid fiber, potassium hydroxide, dimethyl sulfoxide and deionized water is (0.5-4) g: (1-3) g: (400-800) mL: (10-50) mL.
4. The method for preparing the electromagnetic shielding composite paper according to claim 2, characterized in that: In the step a1), the mixing and stirring conditions are: room temperature, magnetic stirring rate of 1000-2000 r / min, and time of 3-5 h; In the step a2), the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min.
5. The method for preparing the electromagnetic shielding composite paper according to claim 1, characterized in that: The preparation of the carbon nanotube dispersion in step b) comprises the following steps: The carbon nanotubes are added into an organic solvent, a dispersant is then added thereto, and the carbon nanotubes are dispersed by ultrasonic treatment to form a carbon nanotube dispersion with a carbon nanotube concentration of 0.13-1 g / L.
6. The method for preparing the electromagnetic shielding composite paper according to claim 5, characterized in that: The organic solvent is ethanol or dimethyl sulfoxide; the dispersant is at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, and the added amount of the dispersant is 5-20% of the mass of the carbon nanotubes; the ultrasonic treatment conditions are: room temperature, ultrasonic power of 300-600w, and time of 5-15min.
7. The method for preparing the electromagnetic shielding composite paper according to any one of claims 1 to 6, characterized in that: The mechanical stirring speed is 1000-8000 r / min, and the time is 5-30 min; the magnetic stirring speed is 500-2000 r / min; and the dropping speed of the mixed solution is 10-20 mL / min.
8. The method for preparing the electromagnetic shielding composite paper according to claim 1, characterized in that: In the step d), the dispersion concentration of the filter cake is 0.05-0.5 g / L; the drying temperature is 80-120° C., and the drying time is 8-20 min; In the step e), the hot pressing treatment conditions are: pressure of 5-20 MPa, temperature of 30-120° C., and time of 5-60 min.
9. An electromagnetic shielding composite paper, characterized in that: Prepared by the preparation method of electromagnetic shielding composite paper according to any one of claims 1 to 8; The thickness of the electromagnetic shielding composite paper is 0.02-0.2 mm; The electromagnetic shielding composite paper has a total electromagnetic shielding effectiveness of 10-60 dB for a frequency of 8.2-12.4 GHz.